Performance Analysis of High Computational Jobs using Infiniband Interconnect (International Journal of Advanced Research in Computer Science, 2017)
The aim of this paper, analyzing the performance of Ethernet using matrix multiplication of higher order with the help of infiniband interconnects system. Second improving the capacity of Ethernet bandwidth from 10 Mbps to 40 Gbps. This paper described the Matrix Multiplication problem which is taken and contain both multiplication and addition factor operations for output of the results. Results will classify the job size to be taken on both interconnect for optimal use of the bandwidth. The whole proposed work will required in open source Linux using MPI. The developed interconnected model has been work in efficient way and it has been shown that this model is faster than the previous infiniband interconnected system and the bandwidth is induced.Keywords: Bioinformatics, mpiBLAST, HPC, Infiniband and Cluster Computing.